Aetiology and diagnostics of paediatric hydrocephalus across Africa: a systematic review and meta-analysis. Issue 12 (December 2022) - Aukrust, Camilla G; Paulsen, Anne Henriette; Uche, Enoch Ogbonnaya; Kamalo, Patrick Dongosolo; Sandven, Irene; Fjeld, Heidi E; Strømme, Hilde; Eide, Per Kristian
Summary: Background: We aimed to identify the aetiological distribution and the diagnostic methods for paediatric hydrocephalus across Africa, for which there is currently scarce evidence. Methods: In this systematic review and meta-analysis, we searched MEDLINE (Ovid), the Cochrane Database of Systematic Reviews (Wiley), Embase (Ovid), Global Health (Ovid), Maternity & Infant Care (Ovid), Scopus, African Index Medicus (Global Index Medicus, WHO) and Africa-Wide Information (EBSCO) from inception to Nov 29, 2021. We included studies from any African country reporting on the distribution of hydrocephalus aetiology in children aged 18 years and younger, with no language restrictions. Hydrocephalus was defined as radiological evidence of ventriculomegaly or associated clinical symptoms and signs of the disorder, or surgical treatment for hydrocephalus. Exclusion criteria were studies only reporting on one specific subgroup or one specific cause of hydrocephalus. We also excluded conference and meetings abstracts, grey literature, editorials, commentaries, historical reviews, systematic reviews, case reports and clinical guidelines, as well as studies on non-humans, fetuses, or post-mortem reports. The proportions of postinfectious hydrocephalus, non-postinfectious hydrocephalus, and hydrocephalus related to spinal dysraphism were calculated using a random-effects model. Additionally, we included a category for unclear cases. Diagnostic methods were described qualitatively. To assess methodological study quality, we applied critical appraisal checklists provided by the Joanna Briggs Institute. The study was registered in Prospero (CRD42020219038). Findings: Our search yielded 3783 results, of which 1880 (49·7%) were duplicates and were removed. The remaining 1903 abstracts were screened and 122 (6·4%) full articles were sought for retrieval; of these, we included 38 studies from 18 African countries that studied a total of 6565 children. The pooled proportion of postinfectious hydrocephalus was 28% (95% CI 22–36), non-postinfectious hydrocephalus was 21% (95% CI 13–30), and of spinal dysraphism was 16% (95% CI 12–20), with substantial heterogeneity. The pooled proportion of hydrocephalus of unclear aetiology was 20% (95% CI 13–28). Interpretation: Our findings suggest that postinfectious hydrocephalus is the single most common cause of paediatric hydrocephalus in Africa. For targeted investments to be optimal, there is a need for consensus regarding the aetiological classification of hydrocephalus and improved access to diagnostic services. Funding: Rikshospitalet, Oslo University Hospital, Oslo, Norway.